PENINGKATAN PENGETAHUAN MASYARAKAT MELALUI PELATIHAN PEMBUATAN LAMPU PELITA BERBAHAN MINYAK JELANTAH DI DESA ASAAN SULTENG - Syarifuddin Achmad; Hasanuddin Hasanuddin; Sunardi Sunardi; Esta Larosa; idham halid lahay (Jurnal Pengabdian Teknik Industri, 2022)
Asaan Village is one of the villages in the Pagimana District, Luwuk Regency, Central Sulawesi Province, which is located 11 km to the south of the Pagimana District. The geographical conditions of the mountains and forest areas with an altitude of 200-500 meters above sea level and an uncertain climate such as changes in temperature, wind, result in frequent disturbances of lighting or blackouts so that people often have difficulty doing activities at night. Meanwhile, to deal with blackouts, people using kerosene lamps only have drawbacks, such as the high price of kerosene and steps in the market. This problem is the basis for carrying out community service activities, and by utilizing used materials such as coconut oil which has been used in the frying or used cooking process, this material is easy to obtain and is not purchased because it is only a waste material. Even though used cooking oil can be made as a lamp to replace electricity when there is a blackout. The service method used is a motivational approach and creative innovation through skills training for the Asaan village community. The results of this activity are 1) The community is assisted by training in making cheap and environmentally friendly lamp lamps, 2) There is alternative community lighting to overcome frequent blackouts, 3) Community creativity increases in processing used cooking oil as an efficient fuel.Keywords: community skills, lamps, used cooking oil.